Long-Term Outcomes of Right Minithoracotomy Versus Hemisternotomy for Mitral Valve Repair. Issue 1 (February 2020) - Percy, Edward; Hirji, Sameer A.; Yazdchi, Farhang; McGurk, Siobhan; Kiehm, Spencer; Cook, Richard; Kaneko, Tsuyoshi; Shekar, Prem; Pelletier, Marc P.
Objective: Minimally invasive mitral valve repair has been increasingly adopted. Right minithoracotomy (RT) and lower hemisternotomy (HS) have each been associated with improved short-term outcomes; however, these approaches have not been directly compared to each other. The aim of this study was to compare long-term survival and durability of 2 minimally invasive approaches to mitral repair. Methods: We retrospectively identified all isolated mitral repairs performed via RT or HS between October 1997 and June 2018; 100 RT cases and 719 HS cases were included. Outcomes of interest were postoperative complications, long-term survival, and freedom from mitral reoperation. A Cox proportional hazard model was used to compare RT and HS to a reference cohort of full-sternotomy cases. Total observation time was 9, 901 patient-years and mean follow-up time was 12.2 years. Results: Mean age was 58±12 years in the RT group and 56±13 years in the HS group ( P = 0.2). The RT group had longer bypass (143 minutes vs. 112 minutes; P < 0.001) and cross-clamp times (99 minutes vs. 78 minutes; P < 0.001) compared with the HS group. There were no differences in operative mortality or 30-day outcomes. Survival at 5, 10, and 15 years was 99% (96-100), 92% (85-100), and 69% (30-100) in the RT group and 98% (97-99), 92% (90-94), and 89% (86-92) for HS ( P < 0.9). There were no differences in risk-adjusted survival between RT, HS and full sternotomy. No long-term mitral reoperations occurred in the RT group and 8 (1%) occurred in the HS group ( P < 0.50). Conclusions: Minimally invasive mitral valve repair can be performed safely through RT or HS with excellent survival and durability at 15 years.